Can resilience promote calling among Chinese nurses in intensive care units during the COVID-19 pandemic? The mediating role of thriving at work and moderating role of ethical leadership - Sun, Tao; Zhang, Shu-e; Yin, Hong-yan; Li, Qing-lin; Li, Ye; Li, Li; Gao, Yu-fang; Huang, Xian-hong; Liu, Bei (Frontiers in Psychology, 2022)
Background: Nurses working in intensive care unit (ICU) clung tenaciously to their job during anti-COVID-19 pandemic in spite of enduring stressed psychological and physical effects as a result of providing nursing care for infected patients, which indicates that they possessed the high-degree professionalism and career calling. The aim of this study is to explain how the joint effect and functional mechanism of resilience, thriving at work and ethical leadership influence the calling of ICU nurse. Methods: From December 2020 to January 2021 during the stage of the anti-COVID-19 pandemic, a cross-sectional survey of fifteen provinces in China was conducted using an online questionnaire. A total of 340 ICU nurses (effective response rate: 64.89%) completed sufficiently responses to be used in the study. Socio-demographic factors, job demographic factors, resilience, calling, thriving at work and ethical leadership were assessed using questionnaires. General linear modeling (GLM), Hierarchical linear regression (HLR) analysis, Generalized additive model (GAM) were performed to examine all the considered research hypotheses. Results: Resilience was positively and significantly associated with calling. Moreover, thriving at work partially mediated the relationship between resilience and calling. The indirect effect of resilience on calling was 0.204 (P<0.0001), and the direct effect of resilience on calling through thriving at work was 0.215 (P<0.0001). Total effect of resilience on calling was 0.419 (P<0.0001). In addition, ethical leadership played a moderating role in the relationship between resilience and calling (β=0.16, P<0.05). Conclusion: Greater resilience can positively predict increased calling among Chinese ICU nurses during anti-COVID-19 pandemic. Moreover, thriving at work is a mechanism that partly transmits the positive effects of resilience on calling. Overall, nurses who possessed greater resilience tend to maintain thriving at work in the face of such adversity, further resulting in subsequently increased calling. Besides, finding suggests that there is stronger influence of resilience on calling among nurses working in an organization under managing by an ethical leader. The current findings may offer two insights for nursing practitioners and policy-makers in the post-pandemic world.